Virulence determinants and antibiotic resistance of Extended-Spectrum Beta-lactamase (ESBL) producing Klebsiella pneumoniae Isolated from hospital environment - Costa, Dorin Teresa D. (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2019.